Lithium fluoride injection layers can form quasi-Ohmic contacts for both holes and electrons - Bory, Benjamin F. (2018)
Thin LiF interlayers are typically used in organic light-emitting diodes to enhance the electron injection. Here, we show that the effective work function of a contact with a LiF interlayer can be either raised or lowered depending on the history of the applied bias. Formation of quasi-Ohmic contacts for both electrons and holes is demonstrated by electroluminescence from symmetric LiF/polymer/LiF diodes in both bias polarities. The origin of the dynamic switching is charging of electrically induced Frenkel defects. The current density-electroluminescence-voltage characteristics can qualitatively be explained. The interpretation is corroborated by unipolar memristive switching and by bias dependent reflection measurements. (C) 2014 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution 3.0 Unported License.